Customer Protection in Cases of Fintech Lending Default: The Perspective of Indonesian Economic Law - Markus Suryoutomo; Hasibatul Isniar Sepbrina Pratiwi S; Mig Irianto Legowo; Amsari Damanik; Ade Ari Gumilar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The rapid development of financial technology (fintech) has fundamentally transformed national financial systems, particularly through the emergence of peer-to-peer (P2P) lending services that enable individuals to obtain funding quickly and easily without the involvement of traditional financial institutions. This business model not only promotes financial inclusion but also drives the growth of Indonesia’s digital economy. Nevertheless, behind its efficiency and convenience, fintech lending poses substantial legal and economic risks most notably the risk of default, which can cause significant losses for both lenders and borrowers. The occurrence of defaults in fintech lending illustrates an imbalance in the legal standing between platform providers, lenders, and borrowers. Within the framework of Indonesia’s economic law, consumer protection serves as a crucial element in maintaining fairness and trust in digital financial systems. This article aims to examine the forms and effectiveness of legal protection available to consumers in cases of fintech lending default, emphasizing the role and responsibility of the Financial Services Authority (Otoritas Jasa Keuangan OJK) as the supervisory body of the financial services sector. This study employs a normative legal research method using statutory and conceptual approaches to analyze the existing regulations and policies, including OJK Regulation No. 10/POJK.05/2022 on Information Technology-Based Joint Funding Services. The findings indicate that, although OJK regulations have established a strong legal foundation, the practical implementation of consumer protection remains challenging particularly in areas of supervision, dispute resolution, and public financial literacy regarding digital finance.